The Terra-Luna Collapse and the Role of the Anchor Protocol: A Bird’s Eye View of the Crash - 최재원; 왕수봉 (재무연구, 2024)
This paper explorers the contributing factors to the Terra (UST)-Luna crash in May 2022. We argue that the crash was primarily fueled by the unsustainable interest rates offered by the Anchor Protocol. Initially, Terra was designed to facilitate fee-free payments and ensure stability through a diversified demand base from payment services. However, the launch of the Anchor Protocol in 2021, with its 19.45% interest rate, shifted UST's focus towards speculative demand. This change led to an unsustainable increase in UST's supply, ultimately triggering a run from Terra. We discuss flaws in the governance mechanism for setting Anchor Protocol's interest rates. The exorbitant yield offered by the Anchor Protocol significantly contributed to undermining Terra's long-term stability. The speculative demand incited by the Anchor Protocol's high interest rates was likely a major factor in the Terra collapse in May 2022.
Keywords: Cryptocurrency; Stablecoin; Financial fragility; Terra(UST)-Luna Crash; Decentralized Savings Protocol